Positive Framing: Does It Work for Promoting Healthier Food Choice? - Bintang Permatasari; Anna Undarwati (Journal of Educational, Health and Community Psychology, 2024)
The increase in overweight and obesity in Indonesia, along with its negative impact on individual health, such as the risk of chronic diseases and reduced life expectancy, cannot be separated from unhealthy food choices. Unhealthy food choices can negatively impact health, including increasing the risk of overweight and obesity. The aim of this study is to investigate potential differences in the impact of positive message framing on healthy eating behavior. The sample of this study involved student participants aged 18-24 years. This study used an experimental design. In this study, participants were divided into experimental and control groups. The experimental group was given positive framing messages, while the control group did not receive any framing messages. Participants conducted a shopping simulation in a virtual supermarket using virtual reality devices. After that, the participants' food choices and shopping scores were analyzed. The results of this study show a significant difference in food choices between participants given positive health cues framing and those who were not. This means that participants in the experimental group who received positive framing messages had healthier food choices than the control group. The use of positive framing strategies, such as through posters, can be effective in promoting healthy eating behavior. The implications of this study provide insights to the community that positive framing messages can be an influential way to encourage healthy eating behavior among the publicKeywords: positive framing; food choice; positive framing messages; healthy food choices.